PERANCANGAN AUGMENTED REALITY SEBAGAI PEMBELAJARAN ANATOMI MANUSIA BERBASIS ANDROID - Apriyanto, Apriyanto; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2023)
Learning is a human effort in understanding basic knowledge. The learning process must meet the interactive, fun, and give students the ability to develop creativity. Interesting learning media must be applied. Human organ material is course that is not easy to understand, if you use books as a literature review. Human organ material is only limited to print media such as presentation, and books. This learning leads to a less interactive understanding, and is too monotonous, as well as learning becomes bored. Augmented reality is a medium that connects the virtual world with the real world. Augmented reality is used to facilitate learning by providing information virtually, not only used for the environment, but combining two-dimensional or three-dimensional virtual then projected into an object in real time. Augmented reality uses the android-based Marker Based Tracking method. Application creation using tools such as Unity, Vuforia, Blender. The system design method uses the System Development Life Cycle (SDLC) method or the waterfall method. The purpose of this study is the formation of an android-based augmented reality application as an interesting and more interactive learning medium for users